PERTUMBUHAN PENJUALAN, FINANCIAL DISTRESS, PREFERENSI RESIKO: APAKAH MASA PANDEMI COVID-19 BERPERAN? - Widayanti, Novita Christy; Damayanti, Theresia Woro (Jurnal Akuntansi Kontemporer, 2022)
Research Purposes. This study aims to examine the impact of sales growth and financial distress on tax aggressiveness and executive risk preference factors as moderating variables and examine the differences in these impacts before and after the COVID-19 pandemic.Research Methods. The design for this study is quantitative research with secondary data. Data were obtained from the quarterly reports of manufacturing companies listed on the Indonesia Stock Exchange in 2019 and 2020. Data analysis technique used are regression analysis and moderated regression analysis (MRA). Then, coefficient difference test is conducted to determine the differences the effect of variables before and after the pandemic. For robustness of moderating variable testing, this study conducts subgroup analysis and compare the result with MRA.Research Result and Findings. The result shows that, during the COVID-19 pandemic, sales growth and financial distress have negative effect on tax aggressiveness. Executive risk preference moderates the effect of sales growth on tax aggressiveness, but executive risk preference does not moderate the effect of financial distress. This study findings have implications to expand the literature related to tax aggressiveness in conditions of the financial crisis due to the COVID-19 pandemic.